The Role of Islamic Boarding Schools in Building Resilience of Students in the Middle of Consumptive Culture (Study at Syaichona Moh. Cholil Islamic Boarding School Bangkalan) - Muhsinin, Muhsinin; Nafis, Abdul Wadud; Ahmadiono, Ahmadiono (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
Building the resilience of Islamic boarding schools and students is very necessary because it cannot be denied that the development of science and globalization and the increasing complexity of new problems that exist in today's life will be a challenge for Islamic boarding schools to continue to survive in today's era. The focus of this research namely regarding the role of the Syaichona Moh. Cholil Islamic Boarding School in maintaining resilience amidst a consumer culture. This research is qualitative. The data in this research comes from primary data and secondary data using observation, interview, and documentation techniques in collecting the data which is then analyzed using interactive analysis. The results of this research show the role of the Syaichona Moh. Cholil Islamic Boarding School in building the resilience of students amid consumer culture includes improving the character education of students by treating consumption as the enemy and providing an example with a simple lifestyle, apart from that, Islamic boarding schools also implement rules of conduct so that students avoid wasteful behavior by implementing pocket money control, prohibitions. leaving the Islamic boarding school, prohibiting shopping in shops other than those belonging to the Islamic boarding school, and keeping students away from various advertisements and technology.